Implementasi Pembelajaran IPA Berbasis Multiple Intelligence pada Internasional Class Program Kelas V MI Masjid Al-Akbar Surabaya - Ramadhiani, Lailatus Syahrina; Nuriza, Khusnul Isma (Prodi PGMI STAI Al-Akbar Surabaya, 2024)
In every lesson, an approach is needed in teaching and learning activities. This approach must be in accordance with what students need to understand each material taught. Especially in science learning. At elementary school level, especially in class V, learning science material requires in-depth understanding, so an approach is needed that takes into account each child's intelligence. In the implementation of science learning, there is an approach called the multiple intelligence approach. In implementing science learning in class V at MI Masjid Al-Akbar Surabaya, the implementation is by combining each science learning method that is appropriate to the material being taught. Learning with multiple intelligence is very appropriate to be applied to science learning. The implementation of science learning based on multiple intelligence means that every child with different intelligence can understand the material presented in science learning. There are obstacles and supporters in implementing multiple intelligence-based science learning in class V. Among these obstacles are the lack of innovation by teachers and the students' uncertain moods. Meanwhile, the supporting factors for implementing multiple intelligence science learning are the availability of various facilities provided by schools as well as collaboration between students, teachers and parents who help each other in approaching multiple intelligence learning in class V.